Leveling Up : Impacts of Performance-Based Grants on Municipal Revenue Collection in Mozambique - Erman, Alvina; Solis Uehara, Carla; Beaudet, Chloé (World Bank, Washington, DC, 2021)
Due to recent decentralization reforms, municipalities now have important responsibilities in the sustainable urban development of Mozambique. This paper assesses the efficiency of World Bank funded municipal performance grants and technical assistance provided to municipalities, to enable municipalities to increase revenue collection. The municipal performance grants transferred resources to municipalities directed by performance-based indicators. The technical assistance program provided classroom and on-the-job training for municipal staff. The effect of a municipal performance grant on revenue collection is found to be positive and the effect is primarily lagged. Receiving a municipal performance grant in years t−1 and t−2 is associated with an increase in revenue collection in year t. Contemporary effects are negative but not significant. However, the positive impact of a lagged municipal performance grant on revenue collection is only significant after 2015, which coincides with implementation of technical assistance. And when municipal performance grants are combined with technical assistance, the contemporary effect of the transfer is also positive and significant. Overall, the impact of the municipal performance grants is larger for towns than cities. For every 10 meticais per capita received in municipal performance grants when combined with technical assistance, revenue collection increases by 10–11 meticais per capita in cities and 24 and 60 meticais per capita in towns. The findings of this study suggest that performance-based grants incentivize local governments with low capacity to collect more revenue. However, the transfers should be accompanied by a technical assistance program that can support capacity building in financial and fiscal management, as well as urban development and investment planning.